Energy retrofit of historic buildings: Environmental assessment of cost-optimal solutions. (December 2015) - Tadeu, S.; Rodrigues, C.; Tadeu, A.; Freire, F.; Simões, N.
Abstract: This paper describes the implementation of an integrated cost optimality and environmental assessment involving alternative energy efficiency retrofit packages for a building that dates from the beginning of the 20th century. A building typical of the building stock in the centre of Coimbra (located in the central region of Portugal and recently classified as a UNESCO World Heritage Site) was used to illustrate the methodology presented. The results were also analysed for the same building in two other locations. A life-cycle (LC) model was implemented to assess different energy efficiency measures for an apartment. The economic assessment complied with European Directive 2010/31/EU. The results show that the lowest life-cycle environmental impacts were obtained for insulation thicknesses between 50 and 120 mm, which are also cost-optimal. It is also shown that insulation thicknesses of more than 80 mm do not improve energy efficiency or global cost reduction. This paper shows that, even though historic buildings in Portugal do not have to comply with building energy codes, significant energy savings can be achieved for them without changing their historic character. It was also concluded that economic and environmental costs can both be minimised by choosing the most suitable energy efficiency retrofit measures. Highlights: Integrated life-cycle assessment and cost optiality. Historic buildings energy efficiency retrofit. Locations with higher energy needs had higher insulation level thresholds. No marginal LC benefit in scednario with 80 mm or more of insulation. Low marginal costs savings for thicknesses greater than 80 mm.